Real-world efficacy and safety of axitinib in combination with anti-programmed cell death-1 antibody for advanced mucosal melanoma. (October 2021) - Tang, Bixia; Mo, Jiazhi; Yan, Xieqiao; Duan, Rong; Chi, Zhihong; Cui, Chuanliang; Si, Lu; Kong, Yan; Mao, Lili; Li, Siming; Zhou, Li; Lian, Bin; et al.
Abstract: Purpose: The combination of vascular endothelial growth factor receptor (VEGFR) inhibitor and programmed cell death-1 (PD-1) blockade provides promising therapeutic opportunities for advanced mucosal melanoma in early phase trials. The aim of this retrospective study was to evaluate the efficacy and safety of the combination regimen for advanced mucosal melanoma in the real world. Methods: Patients with advanced mucosal melanoma received an anti-PD-1 antibody plus the VEGFR inhibitor axitinib until confirmed disease progression or unacceptable toxicity. In addition, those with liver metastasis were allowed to take hepatic transcatheter arterial chemoembolisation (TACE). The primary endpoint was overall response rate (ORR). Secondary endpoints included disease control rate (DCR), time to treatment failure (TTF), duration of response (DOR), overall survival (OS) and treatment-related adverse events (TRAEs). Results: Eighty-one and sixty-six patients received axitinib plus immunotherapy as first-line and salvage therapy, respectively. Overall, ORR was 24.5% (95% CI, 17.3–31.6), DCR was 72.7% (95% CI, 65.3–80.1). Median TTF, DOR and OS were 5.2 months (95% CI, 3.7–6.6), 9.2 months (95% CI, 7.2–11.2) and 11.1 months (95% CI, 7.2–15.0). ORR was 30.0% (95% CI, 19.7–40.3) and 17.5% (95% CI, 7.8–27.1) as first-line and salvage therapy, respectively. No statistical difference among the primary sites was noted for ORR. The ORR of patients with liver metastasis with or without hepatic TACE was 26.1% (95% CI, 6.7–45.5) and 15.0% (95% CI, 2.1–32.1), respectively (P = 0.467). Elevated LDH and poor ECOG status are negative predictive factors. Conclusion: This is the largest analysis of anti-PD-1 plus VEGFR inhibitor therapy for mucosal melanoma to date. Immunotherapy plus anti-angiogenesis is applicable for advanced mucosal melanoma, especially as front-line. Hepatic TACE might act synergistically with systemic immunotherapy and anti-angiogenesis. Highlights: Demonstrate the efficacy of ICIs plus anti-angiogenesis for adMM in the real world. TACE might act synergistically with systemic immunotherapy and anti-angiogenesis. No difference in clinical response among the primary mucosal sites. LDH and ECOG status are predictive for the efficacy of ICIs + anti-angiogenesis for adMM.